Organization Change in Business and Government - Glueck, William F. (Academy of Management Journal, 1969)
This paper discusses organization change in government and business in America. First the causes and dimensions of organization change are presented. The literature on organization change is reviewed and two brief case studies of organization change are presented. Finally, comparisons and contrasts of the process in these two environments are made.